The Biomechanics of Green Plants in The Presence of Environmental Thermal Perturbations - Mba, Nnenna Ude; Abbey, Tamunoimi Michael (European Journal of Applied Sciences, 2024)
This study mimic the flow model of mineral salt solution in green plants when the environmental temperature suddenly increased. The usual Navier stokes equation in cylindrical coordinate is used to formulate the governing system of equations for the flow model. The analysis is then carried out by means of the homotopy perturbation method (HPM). The result obtained shows that the increase in the thermal parameters caused a corresponding increase in the temperature, velocity and the quantity of fluids being transported to the leaves of the plant. It further reveals that when the aspect ratio of the plant is very large, that is for plant whose length is far greater than its diameter, the flow profiles tend to be streamline, laminar and Poiseuille. This understanding shows why some green plants of this nature tend to strive during the period of heat waves and drought. It was further seen that when the thermal parameter the model returns to that of Rand [1] and Bestman [2].